Subcellular Localization of Epstein–Barr Virus BLLF2 and Its Underlying Mechanisms - Li, Jingjing; Guo, Yingjie; Deng, Yangxi; Hu, Li; Li, Bolin; Deng, Shenyu; Zhong, Jiayi; Xie, Li; Shi, Shaoxuan; Hong, Xuejun; Zheng, Xuelong; Cai, Mingsheng; et al. (Frontiers in Microbiology, 2021)
Epstein-Barr virus (EBV), the pathogen of several human malignancies, encodes many proteins required to be transported into the nucleus for viral DNA reproduction and nucleocapsids assembly in the lytic replication cycle. Here, fluorescence microscope, mutation analysis, interspecies heterokaryon assays, co-immunoprecipitation assay, RNA interference, and Western blot were performed to explore the nuclear import mechanism of EBV tegument protein BLLF2. BLLF2 was shown to be a nucleocytoplasmic shuttling protein neither by chromosomal region maintenance 1 (CRM1) nor transporter associated with antigen processing (TAP)-dependent pathway. Yet, BLLF2's two functional nuclear localization signals (NLSs), NLS1 (16KRQALETVPHPQNRGR31) and NLS2 (48PPVAKRRR58), were identified, whereas the predicted NES was nonfunctional. Finally, BLLF2 was proved to transport into the nucleus via Ran-dependent and importin β1-dependent pathway. This mechanism may contribute to a more extensive insight into the assembly and synthesis of EBV virions in the nucleus, thus affording a new direction for the treatment of viruses.